“É o que eles estão querendo pesquisar, estão querendo mostrar”: apropriação de práticas de numeramento da Educação Estatística por estudantes indígenas do Curso de Formação Intercultural para Educadores Indígenas da UFMG - Ruana Priscila da Silva Brito (2019)
In this research, we analyze different ways of appropriation, by indigenous in teacher education, of numeracy practices related to the production of knowledge that is part of and composes a statistical culture. These modes of appropriation were caught in the discursive interactions that took place in classes given to the Mathematics qualification second class of the Intercultural Training Course for Indigenous Educators, Faculty of Education, Federal University of Minas Gerais (FIEI/UFMG). In particular, they focus on the interactions provided at meetings where a workshop was developed to propose and guide the conducting of an opinion poll by indigenous undergraduates and encourage them to do the same work with their students from the indigenous schools of their respective villages. The analysis seeks to recognize, in the positions taken by these subjects in those discursive practices, the tensions that involve the processes of appropriation of concepts, procedures and values related to Statistical Education, understood as an instance of appropriation of social literacy practices in the context of an Indigenous Intercultural Teacher Training Course. Thus, concepts from the field of literacy are mobilized to identify, in those interactions, different dimensions of statistical literacy. For analytical purposes, the concepts of alfabetização, alfabetismo and letramento are distinguished, relating them, respectively, to the statistical literacy, statistical reasoning and statistical thinking dimensions proposed by Ben-Zvi and Garfield (2004) and to the domains of knowledge (conceptual, epistemic and social) proposed by Duschl (2007).